Reaction paths of Ni rich phases: Effect of Ni thickness. (July 2017) - Tellouche, G.; Derafa, A.; Hoummada, K.; Mangelinck, D.
Abstract: The kinetics of growth and consumption of Ni-rich phases is determined from in situ X-ray diffraction measurements performed during isothermal annealing. The results show that the life time of θ-Ni2 Si depends on the initial Ni thickness. A slow kinetic of consumption of θ-Ni2 Si is observed during the reaction of 50 nm Ni with Si substrate, while a fast rate of consumption of θ-Ni2 Si is observed when θ-Ni2 Si is a transient phase. A qualitative model has been proposed to explain the obtained results. Graphical abstract: Schematic of the reaction paths for 150 (Top) and 50 (down) nm Ni film with silicon substrate. Highlights: The phase sequence of Ni rich phases and the consumption kinetic of θ-Ni2 Si phase are modified by the initial nickel thickness. For 150 nm Ni: The consumption of θ-Ni2 Si occurs at δ-Ni2 Si/θ-Ni2 Si interface. For 50 nm Ni: the consumption of θ-Ni2 Si occurs at δ-Ni2 Si/θ-Ni2 Si and NiSi/θ-Ni2 Si interfaces. A qualitative model was proposed to describe the reaction paths of Ni rich phases. The growth and the consumption of θ-Ni2 Si are accompanied by a change in chemical potential.